Indonesia, ASEAN & dinamika Asia Timur : kajian perspektif ekonomi-politik / Zainuddin Djafar ; bebarapa [i.e. beberapa] catatan, Makmur Keliat - Djafar, Zainuddin (Jakarta : Pustaka Jaya, 2008)
On trade relations between Indonesia, ASEAN, and Far East countries
Daftar kepustakaan : 180-182
Keywords: ASEAN; Indonesia -- Foreign relations -- Southeast Asia; Southeast Asia -- Foreign relations -- Indonesia; Indonesia -- Foreign relations -- East Asia; East Asia -- Foreign relations -- Indonesia